(untitled) (Research, Society and Development, 2023)
In an archaic conception, health care was considered a female practice, because it showed signs of weakness, insecurity and fear, characteristics unusual to masculinity in this perception. With this, the presence of men in health services, especially in primary care, has always been considered deficient, as the theories structured in society about health care distance men from these services. The present work aims to seek possible factors that lead men to seek health services less. LILACS, BDENF, SciELO and MEDLINE databases were searched through the VHL and PubMed, articles from 2007 to 2022, in Portuguese, English and Spanish. After inclusion and exclusion criteria, 25 articles were selected. The main factors that evidence the absence of men in health services are: the sociocultural ideals historically imposed on society, lack of time and availability, lack of concern for preventive actions, fear of discovering some disease, delay in care, absence of specialists, among others. Therefore, it is considered that by applying the proposals of the National Policy for Integral Attention to Men’s Health, and by developing actions that encourage men to seek health services, it will be possible to include them in health care, making them feel part of this service and come back again and again.